2020
DOI: 10.1016/j.envpol.2020.115286
|View full text |Cite
|
Sign up to set email alerts
|

Smoked cigarette butt leachate impacts survival and behaviour of freshwater invertebrates

Abstract: Smoked cigarette filters a.k.a. "butts", composed of plastic (e.g. cellulose acetate) are one of the world's most common litter items. In response to concerns about plastic pollution, biodegradable cellulose filters are being promoted as an environmentally safe alternative, however, once smoked, both contain toxins which can leach once discarded. The impacts of biodegradable butts as littered items on the receiving environment, in comparison with conventional butts has not yet been assessed. A freshwater mesoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 27 publications
1
16
0
2
Order By: Relevance
“…Toxicity due to the presence of CB in aquatic environments has been demonstrated by numerous investigations including different marine species from unicellular organisms such as foraminifera [25] to larger ones such as invertebrates and fish [22,26]. Environmental groups have expressed concerns for marine creatures that ingest littered filters [8,27].…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity due to the presence of CB in aquatic environments has been demonstrated by numerous investigations including different marine species from unicellular organisms such as foraminifera [25] to larger ones such as invertebrates and fish [22,26]. Environmental groups have expressed concerns for marine creatures that ingest littered filters [8,27].…”
Section: Introductionmentioning
confidence: 99%
“…In a closed system, however, such as a rockpool, biodegradable cigarette butts would likely cause similar effects to non-biodegradable cigarette butts due to the retention of leachate in the water (Booth et al 2015). Indeed, a recent experiment in a closed freshwater system showed that biodegradable cellulose butts had similar detrimental effects as plastic cellulose acetate butts; causing mortality and a reduction of movement of four invertebrate species (Green et al 2020). Cigarette butts, regardless of their biodegradability, pose a threat as litter in the environment and need to be disposed of appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative cellulose filters have been described as "green", "biodegradable" and "environmentally friendly" implying they would be benign as litter (Amos et al 2017). A recent experiment, however, found that leachate derived from cellulose cigarette butts had the same detrimental effects on freshwater invertebrates as leachate derived from cellulose acetate cigarette butts (Green et al 2020). The comparative effects of cellulose acetate versus cellulose cigarette butts have not yet been tested in a marine system.…”
Section: Introductionmentioning
confidence: 99%
“…Belzagui et al recently showed that microfibers from degraded CBs enhanced the toxicity of CB leachate to freshwater zooplankton (Daphnia magna) in experimental 48 h toxicity tests, suggesting that the microfibers pose an intrinsic risk to small aquatic animals [90]. In another recent study, Green et al compared the toxicity of leachate from conventional plastic cellulose acetate CBs and cellulose CBs, which are being promoted as a biodegradable and environmentally safe alternatives [219]. Both smoked butt types exhibited toxicity to, and decreased activity in, freshwater snails (Bithynia tentaculate).…”
Section: Non-mammalian Animalsmentioning
confidence: 99%